Toxoplasmóza u imunokompromitovaných pacientů - Machala, L; Kodym, P; Malý, M; Geleneky, M; Beran, O; Jilich, D (Epidemiologie, mikrobiologie, imunologie, 2015)
In humans, toxoplasmosis mostly occurs as a latent infection, but in immunocompromised individuals, the agent may reactivate and cause severe to life-threatening disease. HIV positive individuals and transplant recipients, in particular hematopoietic stem cell transplant and heart transplant recipients, are at highest risk. The disease most often affects the central nervous system but can involve any organ. Because of the alteration of the immune response in these patients, the serodiagnosis is not reliable and direct detection of the causative agent is needed--namely by microscopy and DNA PCR. If inadequately treated or left untreated, toxoplasmosis generally has a fatal prognosis in immunocompromised patients and therefore, the treatment must be started as early and energetically as possible. The gold standard both in the treatment of reactivation and secondary prophylaxis is the pyrimethamine-sulfadiazine combination while co-trimoxazole can be used in the primary prophylaxis for high-risk patients.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; Toxoplasmosis; toxoplazmóza; Anti-Infective Agents; Hematopoietic Stem Cell Transplantation; Immunocompromised Host; sérologické testy; Trimethoprim, Sulfamethoxazole Drug Combination; kombinace léků trimethoprim a sulfamethoxazol; transplantace hematopoetických kmenových buněk; Humans; antiinfekční látky; Serologic Tests; Toxoplasma; lidé; imunokompromitovaný pacient